Arboridinine, a Pentacyclic Indole Alkaloid with a New Cage Carbon–Nitrogen Skeleton Derived from a Pericine Precursor - Wong, S.P.; Gan, C.Y.; Lim, K.H.; Ting, K.N.; Low, Y.Y.; Kam, T.S. (American Chemical Society, 2015)
A new monoterpene indole alkaloid characterized by an unprecedented pentacyclic cage skeleton, arboridinine (1), was isolated from a Malaysian Kopsia species. The structure and absolute configuration of the alkaloid were determined based on NMR, MS, and X-ray diffraction analysis. A possible biogenetic pathway from a pericine precursor is presented.